Deformation and Fracture of Silica Glass Fiber Under Sharp Wedge-Indentation - Sajzew, Roman; Limbach, Rene; Wondraczek, Lothar (Frontiers in Materials, 2020)
Wedge-indentation provides a means for overcoming some of the problems of normal indentation on curved glass surfaces. In particular, it enables testing in comparably homogenous, two-dimensional stress fields, avoiding the effects of the sharp edges of pyramidal indenters. Adjusting the wedge’s opening angle, length and orientation relative to the fiber surface enables highly reproducible studies of material deformation, surface crack initiation and effects of fiber anisotropy.